AUTHORITY OF THE HOUSE OF REPRESENTATIVES IN THE STATE SYSTEM REPUBLIC OF INDONESIA UNDER THE CONSTITUTION OF THE REPUBLIC OF INDONESIA YEAR 1945 - Rosidi, Ahmad (Jurnal IUS (Kajian Hukum dan Keadilan), 2015)
The purpose of the establishment of the DPD is philosophically driven more by the interests of the colouring of national government policy to provide new space for the benefit of local communities. Definition of the area here is certainly not an area, but geo-cultural area in the frame that compoundIn this study described some problem formulation, among others; How Politics Law Establishment of the Regional Representative Council in the state system in Indonesia, how the position of Regional Representative Council in the formulation of Law, How Concept notch setting functions in the formation of the Regional Representatives Council Act forward. Study is a normative legal research, approach used is statutory approach, conceptual approach, doctrinal approach. Techniques of collecting legal material accordance with the use of secondary materials in this study, the collection done by gathering, assessing, and treating systematically library materials and documents related. Secondary data concerning the primary legal materials, secondary and tertiary derived from library materials, with due regard to the principle of the update. The data is compiled systematically, in order to obtain a relatively complete picture of the qualitative classification. Based on the results of this study suggested that, in the field of legislative regulation of the authority of the Regional Representative Council as stipulated by Article 22 D Paragraph (1) and (2) of the Constitution of the Republic of Indonesia in 1945 contrary to the desired status and condition of the formation of the Council Regional Representative, then the arrangement of authority in the field of the legislation need to be changed to conform to the status and conditions of the Regional Representative Council which is the regional representative institutions. And As a concrete step of setting an ideal to the existence and position of the Regional Representative Council, it is necessary to do the changes to the provisions of Article 22 D Paragraph (1) and (2) of the Constitution of the Republic of Indonesia in 1945, by the Peopleâs Consultative be authorized to change and establish the Constitution.Key wordÂ  : Authority Of The House Of Representatives, State System Republic Of Indonesia